Comprehensive education program for diabetes mellitus patients aimed at optimizing quality of life - Contreras, Dr. Freddy (Gaceta Médica de Caracas, 2020)
Epidemiological data show that Diabetes Mellitus (DM) is becoming the epidemic of the 21st century. Numerous studies indicate that good control of DM requires a patient trained in knowledge related to the clinical condition he presents. This work describes a comprehensive education program for DM patients optimizing their quality of life, under the ontological assumption of the interpretation of thought, opinion, experience, and reality perceived by the patient himself. Los datos epidemiológicos muestran que la diabetes mellitus (DM) se está convirtiendo en la epidemia del siglo XXI. Numerosos estudios indican que un buen control de la DM requiere de un paciente entrenado en conocimientos relacionados con la condición clínica que presenta. Este trabajo describe un programa de educación integral para pacientes con DM optimizando su calidad de vida, bajo el supuesto ontológico de la interpretación del pensamiento, opinión, experiencia y realidad percibida por el propio paciente.